On TESOL '84. A Brave New World for TESOL. Selected Papers from the Annual Convention of the Teachers of English to Speakers of Other Languages (18th, Houston, Texas, March 6-11, 1984) - Teachers of English to Speakers of Other Languages; Larson, Penny; Teachers of English to Speakers of Other Languages ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Presented in this volumer are selected convention papers on topics in teaching English as a second language (ESL). Topics include literacy vs. literate skills; ESL development among preschool children in Singapore; language proficiency and comprehension of anaphoric subject pronouns in bilingual and monolingual children; the ESL noise test and cultural differences in affect and performance; affect in the communicative classroom; the development and influence of assimilative motivation; communicative value and information processing in second language acquisition; conditions on interlingual semantic transfer; diary studies and participant observation differences; effective instructional methods; reconciliation of traditional and communicative approaches; a psycholinguistic model of the Chinese ESL reader; ESL curriculum innovation and teachers' attitudes; a functional ESL syllabus in Papua New Guinea; practical applications of the intensive method; evaluating an elementary school program; content area instruction for elementary school ESL students; designing a minicourse for nonnative speakers of English in a chemistry lab course; using computers to teach composition; ESL reading skills instruction; listening activities for small groups; intensive English in traditional academic settings; effective ESL program administration; nonnative teacher preparation; training foreign teaching assistants; and local acceptability in selecting an ESL teaching model. (MSE)
Availability: Teachers of English to Speakers of Other Languages, 1118 22nd St. N.W., Washington, DC 20037 ($13.00).
ERIC Note: For individual papers, see FL 015 006-030.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Techniques; Educational Research; Elementary Secondary Education; English (Second Language); Language Proficiency; Language Research; Program Administration; Program Design; Second Language Instruction; Second Language Learning; Teacher Education; Teaching Methods; Content Area Teaching; Collected Works, Proceedings